Disputa de frames e hibridismo organizacional : um estudo de caso em um hospital universitário federal - Avelar, João Vitor Ramiro (2016)
The hybrid character of teaching hospitals of Brazilian federal universities is configured from its genesis: the side of public health care, promotion of education and research takes place. Contemporary demands of these organizations require appropriate m